IMPLEMENTASI SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE UNTUK PENENTUAN TEMPAT PEMBUANGAN AKHIR - Windarto, Yudi Eko; Windasari, Ike Pertiwi; Arrozi, Moh. Aufal Marom (Jurnal Pengembangan Rekayasa dan Teknologi, 2019)
Garbage is a difficult problem to solve. Data in the Environmental sector still uses traditional or manual methods in processing. Data processing needs to be done to get accurate data and spreading the information more effectively and efficiently. Traditional or manual methods are irrelevant. It needs a system that makes data processing more effective, efficient and accurate.Simple Multi Attribute Ranking Technique (SMART) is one of various Decision Support System methods that can provide assistance, efficiency and accuracy when processing of data. This method will be implemented in data processing to determine the best Final Disposal Areas (FDA) in the districts and will showing visually using a Geographic Information System (GIS). With the presence of this system, it will provide an overview of the best areas for final disposal areas to be built in the districts. In this case, data processing is carried out in Pemalang District, Central Java Province.The fundamental difference between the SMART Method and the other methods is its simplicity and efficiency in processing multi criteria data. Parameters that greatly affect the ideal or are Land Use and Hydrogeology. This Geographic Information System provides the main menu, criteria weight values, relative weight values, alternative values and criteria, assessment and mapping factor values.